SIKAP REMAJA TERHADAP KEPERCAYAAN MARAPU DI KABUPATEN SUMBA TIMUR NUSA TENGGARA TIMUR - Fredy Ngguli Mbulur; TA. Prapancha Hary (JURNAL SPIRITS, 2013)
ABSTRACTThis study aims to determine adolescent attitudes towards trust Marapu in Sumba Timur Waingapu Nusa Tenggara Timur. This study uses qualitative methods. Three research subjects who are teenagers in Waingapu City, Sumba Timur. Data was collected through interviews and observation. Data analysis was performed using the technique of thematic Phenomenal Phsykologi Empherical procedures (EEP). Adolescent attitudes toward trust Marapu Waingapu City Sumba Timur, Nusa Tenggara Timur based cognitive component is known that most adolescent do have a fairly good knowledge about Marapu beliefs , but this does not affect the views and beliefs of the trust Marapu . Most of the youth in the region have a negative outlook and confidence to trust Marapu . Therefore , most of the teenagers are less interested in teaching Marapu . However , they argue that the trust actually Marapu not against religion and government regulations . Based on the affective component is known that the majority of adolescents do not attend the event and participate in the establishment Marapu teaching Marapu teachings. This does not make them feel guilty for Marapu teachings contrary to their religion . However , there are also adolescent who attended the event as well as participate in the establishment Marapu teachings Marapu teachings . There is a sense of guilt if not attended school Merapu because if not present then he was not able to understand Marapu teachings and values of the prevailing culture.Â Keywords: trust marapu, adolescent, attitude